Salivary electrolytes in psoriasis: A preliminary study - Singh Gurcharan; Rajashekar T; Krishnamurthy; Haneef Nayeem Sadath (Indian Journal of Dermatology, 2006)
Background: There have been few isolated studies on alteration of salivary electrolytes in psoriasis but this subject has not been pursued extensively. Purpose: The present study was conducted to assess any alteration in the levels of salivary electrolytes in psoriasis and to correlate the same with type and severity of the disease. Materials and Methods: Fifteen patients of uncomplicated psoriasis and 12 age and sex matched controls attending the outpatient department of R.L.J.H. and S.N.R. Hospitals, Kolar, India were included for analysis of salivary electrolytes. PASI scoring was used to assess the severity of the disease. Student′s t-test ( P < 0.05; significant) was utilized for statistical evaluation of results. Results: Salivary sodium levels were significantly elevated in psoriasis ( P value 0.002), whereas there was no significant rise in levels of salivary potassium. However, potassium levels correlated significantly with severity of the disease ( P value 0.043). Conclusion: There was elevation of salivary sodium levels in patients of psoriasis and potassium levels correlated with severity of the disease. Limitation: Unicentre hospital based study with small sample size; hence the results cannot be generalized.